Haemophilia A in a Female: Study of a Family Using Intragenic and Extragenic Restriction Site Polymorphisms - Piétu, G; Thomas-Maison, N; Sié, P; Larrieu, M J; Meyer, D (Thrombosis and Haemostasis, 1988)
Restriction fragment length polymorphisms(RFLPs) were studied in a large Algerian family which includes 6 haemophiliacs and a previously described case of female haemophilia A. The female propositus is 66 years old with a normal karyotype. Her parents are first cousins. Her 3 sons are haemophiliacs and her 3 daughters with affected children are obligate carriers. The proband has an excessive bleeding tendency and markedly reduced levels of F. VIII (VIII C 0.03 U/ml, VIII Ag 0.01 U/ml) with elevated vWF Ag (2.30 U/ml), similar to the levels observed in affected males from the family. Four RFLPs can be identified by Southern blotting after digesting genomic DNA with the restriction enzymes Bcl I, Bgl I, Kpn I/Xba I and Taq I and hybridization with a 647 bp Stu I/Sca I F. VIII genomic probe, a 1.8 Kb EcoRI F. VIII cDNA probe, a 1.0 Kb EcoRI/Sst I fragment of intron 22 and the extragenic probe ST 14, respectively. With these four RFLPS, the propositus was found to be homozygous for the alleles segregating in this family with the abnormal X-chromosome. The carrier status was proven in a granddaughter and excluded in another. In conclusion, this RFLP linkage analysis is another argument to suggest that the propositus, a rare case of female haemophilia, is homozygous for the abnormal gene.
Keywords: Haemophilia A; Restriction fragment length polymorphism